Isolation And Test Potential Of Phosphate Solubilization Microorganisms On Andisols Sinabung Eruption Impact On Some Thickness Of Ash In Karo District - Nofriyanto Pakolo; Mariani Sembiring; Abdul Rauf (Jurnal Pertanian Tropik, 2018)
Andisol soil erupted ash sinabung has a thickness level, where each thickness has microbial activity and nutrient status of soil who different. This study aims to determine the potential of phosphate solubilization microorganisms on soil erupted ash sinabung. This research was conducted at Soil Biology Laboratory of Faculty of Agriculture USU, which the isolation of microorganisms is fungi and bacteria from the soil erupted Sinabung in some ash thickness to get the isolates to be tested the potential solubility. Isolate tested for their solubility potential in two ways: solid pikovskaya medium with source of phosphate Ca3(PO4)2, AlPO4, FePO4, and RP (Rock Phosphate) and in Andisol soil incubation with microbial dose as much as 1 ml. The result showed that there were 6 isolates of fungi (J1-J6) and 6 bacterial isolates (B1-B6) and the provision of phosphate solubilization microorganisms on Andisol soil has different potential in increasing microbial population, soil respiration, P-total soil, P-available soil, but can decrease C-organic soil with soil acidity degree (pH) and each type of MPF isolate tested will be able to dissolve P-not available to be P-available on solid pikovskaya medium with source of phosphate Ca3(PO4)2, AlPO4, FePO4 and Rock Phosphate but have different capabilities